Implementasi Kompetensi Manajerial Kepala Madrasah dalam Meningkatkan Kinerja Guru di Madrasah Ibtidaiyah Negeri 2 Lamongan - Sa'diyah, Urfa Nailatus; Mukhlishah, Mukhlishah; Sholihah, Ni’matus (Cakrawala : Jurnal Kajian Manajemen Pendidikan Islam dan Studi Sosial, 2024)
The managerial implementation of the madrasah head is important in improving teacher performance.With good managerial skills, teacher performance is maximised and has an impact on the quality of graduates.The purpose of the study was to describe the implementation of the madrasah principal's managerial competence in improving teacher performance at MIN 2 Lamongan.The type of research is descriptive qualitative research,data collection techniques: observation,interviews,documentation. Research subjects: Head of Madrasah, Head of Curriculum, School Committee, Teachers, Students. The results showed:(1) In the managerial application, the madrasah head plans the needs of teachers, conducts the recruitment and selection process of teachers,conducts coaching and professional development of teachers, and provides welfare for teachers at MIN 2 Lamongan;(2)Teacher performance at MIN 2 Lamongan has been running optimally, teachers make lesson plans and syllabus; implementing learning creatively according to the material and character of students,conducting assessments and following up on learning outcomes, teachers actively develop themselves into professional teachers by attending workshops and training;(3)The managerial implementation of the madrasah head in improving teacher performance is carried out by dividing job desks according to teacher qualifications, the madrasah head conducts PKG every 6 months;(4)Supporting factors: managerial skills, supportive environment, teacher dedication, inhibiting factors: funds, miss communication.